Prevalence of hemoglobin variants and their effect on Hba1c measurement among the indigenous population of north Bengal attending a tertiary care hospital - Soutrik Roy; Indrajit Nath; Sayantan Dasgupta; Kumar, Arun; Utpal Kumar Biswas (Asian Journal of Medical Sciences, 2022)
Background: Several forms of hemoglobin variants might be present in the population being fully or partially silent. Furthermore, a high percentage of the population is already suffering from type 2 diabetes mellitus (DM) which is mainly monitored by HbA1c estimation. As the structure of hemoglobin molecule is altered by the variant status hence, this might have an impact on the HbA1c estimation. Aims and Objectives: The study aimed to assess the prevalence of hemoglobin variant and its effect on the HbA1c estimation. Materials and Methods: Samples from 439 individuals were taken and evaluated for any hemoglobin variants,andalso, the HbA1c values were measured. Results: About 27.4% of the study population were found to have hemoglobin variants, out of this 27.4%, 19.5% were Hb E carrier and 6.45% were Hb E diseased. About 22.3% of the population were suffering from DM. Hb variants had significant effect on HbA1C measurement in the overall study population and in the normal population with P<0.001. Two-way ANOVA also showed Hb variant and diabetes status significantly affected HbA1C value with P<0.001 in the study population. Conclusion: All the patients should be properly evaluated for Hb variants before interpreting the results of Hb A1C to prevent improper management.